Discrete mathematics and its applications - Rosen, Kenneth H (Tata McGraw-Hill, 2003)
Discrete mathematics and its applications / Rosen, Kenneth H.. -- New Delhi: Tata McGraw-Hill, 2003 511.3 R813e5 5th ed.